서울 영등포구의 저영향개발에 대한 홍수 완화 전략에 관한 포괄적인 연구 - 마하라니자키; Maharani Zaki; 김재경; Kim Jaekyoung; 임저스틴희준; Lim Justin Heejoon (한국조경학회지, 2024)
본 연구는 Storm Water Management Model(SWMM)의 저영향개발(Low Impact Development, LID) 시나리오를 활용하여 서울시 영등포구의 홍수 완화 효과를 평가하였다. 대상지를 산업지역(Block I)과 주거 및 상업 혼합지역(Block II)으로 구분하고, LID 시나리오 적용이 홍수 유출에 미치는 영향을 탐구하였다. 옥상정원과 빗물 저금통같이 건물에 설치 가능한 저영향 개발 시나리오(Scenario I)와 투수성 포장, 침투도랑, 식생수로, 빗물정원 등과 같은 옥외공간에 설치 가능한 시나리오(Scenario II)를 총 6가지로 구분하여 LID 시나리오를 설계하였다. 현재 서울시 영등포구의 배수 네트워크 지도와 과거 홍수 이벤트의 강우 데이터를 강수 시나리오로 해석하였다. 본 연구의 결과, 적용된 LID 시나리오는 Block I에서 유출량을 26.8%, 첨두 유출량을 7.5% 감소시킬 수 있었으며, Block II에서는 유출량 21.1%, 첨두 유출량 12.6%를 저감하였다. Scenario I에 비해 Scenario II가 관망 노드 홍수 저감에 더 큰 영향을 미쳤으며, 시나리오간 상호작용을 확인할 수 있었다. 건축물 기반의 LID 시나리오는 표면 유출량과 첨두 유출량을 효과적으로 줄이지 못한다는 결과를 확인할 수 있었다. 연구에서 제안된 방법론 및 결과는 도시의 홍수 회복탄력성 및 미래 도시 설계에 기여 가능한 솔루션으로 활용될 것으로 판단된다. This study evaluates the effectiveness of different Low-Impact Development (LID) scenarios in mitigating urban flooding in Yeongdeungpo-gu, Seoul, using the Storm Water Management Model (SWMM). Two key areas, an industrial zone, and a mixed residential-commercial zone, were chosen to explore how different LID implementations impact runoff. The study considers six types of LIDs, including green roofs and rain barrels for building-based scenarios; and permeable pavements, infiltration trenches, vegetative swales, and rain gardens for open space-based scenarios. The drainage network map and historical rainfall data from previous flooding events were applied in SWMM for simulation modeling using different LID scenarios: building-based, open space-based, and combined LID methods. Results show that the combined LID approach is the most effective method, reducing runoff by 26.8% and 21.1% and lowering peak runoff volumes by 7.5% and 12.6% for Block I and Block II, respectively. These scenarios demonstrate that Scenario II has a more significant impact compared to Scenario I, despite the amount of coverage area. In general, building-based LID measures alone show the least reduction in both surface runoff and peak runoff volumes. The proposed approach offers a robust solution that can shape a resilient and livable urban future.